O processo de construção da memória da Revolução Farroupilha - Scheidt, Eduardo (Revista de História, 2002)
This article analyses the processes of the construction of the memory about the Farroupilha Revolution in the historiography, since XIX century until recent years. We found out that, along the years, it has appeared several and contrary versions about the movement, particularly with reference to the "separatism" or "non separatism" of the farrapos and in respect of the presence or lack of influences from the Rio de la Plata countries in the Farroupilha Revolution.